Nimbolide attenuates complete Freund's adjuvant induced arthritis through expression regulation of toll‐like receptors signaling pathway. (27th November 2022) - Israr, Maham; Naseem, Nadia; Akhtar, Tasleem; Aftab, Usman; Zafar, Muhammad Shoaib; Faheem, Muhammad Asif; Shahzad, Muhammad
Abstract: Nimbolide is an active constituent of Azadirachta indica and is known for its anti‐inflammatory, anti‐oxidant, immune‐modulatory, and anti‐cancer effects. Few studies suggest that nimbolide treatment influences the responses to rheumatoid arthritis, but the underlying molecular mechanisms involved are not yet well established. Therefore, the present study was designed to determine the effect of nimbolide on expression regulation of toll‐like receptors to attenuate rheumatoid arthritis. The rheumatoid arthritis model was established by injecting complete Freund's adjuvant (CFA) intra‐dermally into the sub‐plantar region of the left hind paw of rats. Nimbolide (20 mg/kg) and piroxicam (10 mg/kg) were given to arthritic rats. Rats treated with nimbolide showed a significant reduction in inflammatory cells, rheumatoid factor, ESR, and improved the body weight. The results indicated that nimbolide possesses the capacity to attenuate rheumatoid arthritis by downregulating toll‐like receptors, IL‐17, IL‐23, HSP70, and IFN‐γ expression levels. Nimbolide treatment showed significant reduction in the severity of inflammation and destruction of joints and showed comparable effects to piroxicam, which is a standard non‐steroidal anti‐inflammatory drug used for the treatment of rheumatoid arthritis. It can be concluded that nimbolide can be considered as a potential candidate for therapeutic targeting of the toll‐like receptors pathway in rheumatoid arthritis.